The Function of the Ovaries after Menopause - Nunes, Elsa Filipa Henriques Roque (2024)
Introduction Removal of ovaries and fallopian tubes at the same surgical time as hysterectomy (prophylactic bilateral salpingo-oophorectomy) is a frequent practice performed with the main objective of preventing ovarian cancer. Although there is consensus that prophylactic bilateral oophorectomy in premenopausal women should not be performed in populations at low risk of ovarian cancer, as it has harmful effects on women's health and increases long-term mortality rates, evidence on the effects of postmenopausal prophylactic bilateral oophorectomy are controversial and this procedure remains a regular practice. Some studies have shown that postmenopausal ovaries continue to produce androgens, which may play an important role in cardiovascular health, bone remodeling, sexual function and cognitive function. The association between estrogen deficiency and osteoporosis is well known. New evidence has also revealed a possible impact of androgens on bone mineral density (BMD). In postmenopausal women, combined treatment with testosterone and estrogen was more effective in increasing BMD than estrogen alone. However, although most studies have revealed an association between endogenous androgens and BMD, particularly testosterone, others have not reported such an association. Estrogen deficit is responsible for vulvovaginal atrophy and higher incidence of postmenopausal dyspareunia. Few studies have evaluated the relationship between androgens and sexual function in postmenopausal women. Androgens appear to play a role in maintaining sexual health, and clinical trials have consistently shown that testosterone therapy improves sexual function in women with hypoactive sexual desire. Estrogen plays an essential role in the brain and postmenopausal women with higher levels of estradiol have better global cognitive function, but some studies have revealed contradictory results. Likewise, the influence of androgens on postmenopausal cognitive function is not well understood. A positive association between verbal learning and memory and physiological concentrations of exogenously administered testosterone has been reported. However, other studies have shown that lower levels of endogenous testosterone are associated with improved cognitive function or have shown no association. Taking into account that, with the increase in average life expectancy, the postmenopausal period is getting longer, it is essential to know the impact that the removal of the ovaries can have on the longevity and quality of life of these women. The present study aims to clarify the effect of postmenopausal bilateral oophorectomy on serum levels of steroid hormones and the impact they have on bone mineral density, sexual function and cognitive function in older women. Materials and methods In the period from January 1, 2017 to June 30, 2019, 203 postmenopausal women consented to participate in the study. All had intact ovaries at the time of menopause and none had been on hormone replacement therapy. Other general exclusion criteria were the presence of ovarian pathology, current or previous treatment with corticosteroids, alcoholism, narcotic dependence and chronic liver or kidney disease. Each participant underwent a blood collection and serum measurements of 17bestradiol (E2), dehydroepiandrosterone (DHEA), testosterone and androstenedione were performed using gas chromatography associated with mass spectrometry (GCMS/ MS). Four cross-sectional studies were performed. In the first study, postmenopausal women undergoing hysterectomy for benign conditions were divided into two groups: 18 women undergoing hysterectomy alone and 11 women undergoing hysterectomy with prophylactic bilateral salpingo-oophorectomy. Differences in hormone levels in both groups were determined. In the second study, 68 women aged over 65 years underwent bone osteodensitometry using the dual-energy X-ray absorptiometry (DXA) technique, and associations between hormone levels and T-score values of the lumbar spine and femoral neck were evaluated, controlling for confounding variables. In the third study, which included 84 sexually active women, associations between hormone levels and scores in the domains of female sexual response assessed by the Female Sexual Function Index (FSFI) questionnaire were evaluated, with adjustment for confounding variables. The fourth study included 147 women who completed the Montreal Cognitive Assessment (MoCA) test to assess cognitive function and determined associations between hormone levels and cognitive function parameters (global cognitive function, executive function, visuospatial ability, short-term memory , attention, concentration and working memory, language, orientation in time and space), controlling for confounding variables.